DIPLOMASI INDONESIA DI UNITED NATIONS PROGRAM OF ACTIONS (UNPOA) UNTUK MENGATASI ANCAMAN SMALL ARMS AND LIGHT WEAPONS (SALW) - Denik Iswardani Witarti; Budi Hartono (Jurnal Studi Diplomasi dan Keamanan, 2016)
Cold War hasbecome the “golden era” for the trade of conventional weapons. Super power states such as United States and Soviet Union were massive suppliers of weapons for theirsatellite countries. After the Cold War, these weapons are not used and flow to the black market. This poses as a problem because these weapons can flow into areas that are in conflict, suchas areasin Indonesia, especially in Maluku, Poso, Aceh, and Papua. The conflict in respective areas escalated because of the flow, especially the manifold of Small Arms and Light Weapons(SALW). In order to preserve the territorial integrity and safety of the nation from the armed conflict, one of Indonesia’s effort is through diplomacy in the United Nations Program of Action (UNPoA). With descriptive qualitativeapproachand using secondary data, this paper will see how Indonesiandiplomacy in UNPoA in order to face the circulation of illegal SALW aiming to maintain the territorial integrity and national security.